2006
DOI: 10.1186/1475-2875-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Personal protection of long lasting insecticide-treated nets in areas of Anopheles gambiae s.s. resistance to pyrethroids

Abstract: Background: The development of mosquito nets pre-treated with insecticide, Long Lasting Impregnated Nets (LLINs) that last the life span of the net, is a solution to the difficulty of the reimpregnation of conventional nets. Even if they showed a good efficacy in control conditions, their efficacy in the field, particularly in areas with resistance of Anopheles gambiae to pyrethroids, is not well documented. This study compares wide (Olyset ® ) and small (Permanet ® ) mesh LLINs in field conditions, using ento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…A representative sample of 118 adult females was identified by species diagnostic PCR [32]. In agreement with previous studies in the area [26,33-35], all genotyped individuals belonged to the species An. coluzzii , suggesting that almost all, if not all, mosquitoes included in this study belonged to this species.…”
Section: Methodssupporting
confidence: 54%
“…A representative sample of 118 adult females was identified by species diagnostic PCR [32]. In agreement with previous studies in the area [26,33-35], all genotyped individuals belonged to the species An. coluzzii , suggesting that almost all, if not all, mosquitoes included in this study belonged to this species.…”
Section: Methodssupporting
confidence: 54%
“…Control failure attributed to insecticide resistance has been observed after IRS campaigns in South Africa [2,29] and the island of Bioko [4]. While historically in some West African countries ITN/LLINs provide some protection against kdr resistant Anopheles populations [30-32], that situation appears to be changing with selection of additional metabolic mechanisms [27,28]. In Burundi, the high frequency of kdr did not lead to a loss of efficacy of IRS [24,33].…”
Section: Discussionmentioning
confidence: 99%
“…This data closely matches results of the bioefficacy analysis of cyfluthrin impregnated nets which reported a mortality rate on susceptible mosquitoes ranging from 60 to 100% during the first four months after bed net impregnation and a mortality rate ranging from 50 to 90% during the first 5 months after reimpregnation [25]. Although LLINs keep their efficacy even after several washings [37,38,42], a low insecticidal activity and personal protection were demonstrated in West Africa with several varieties of these nets [43]. In addition, recent field evaluation studies reported limited efficacy of LLINs against pyrethroid resistant mosquitoes [44].…”
Section: Discussionmentioning
confidence: 99%